2003
DOI: 10.1016/s0277-9536(02)00548-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutual influences of general practitioners in partnerships

Abstract: The aim of this study was to find out whether or not general practitioners (GPs) within the same partnership show more similarities in attitudes and behaviour than GPs in different partnerships, and what the causes of these similarities might be. Knowledge of the causes of patterns of similarities within medical teams contributes to understanding medical practice variation, which is crucial in developing effective health care policies.Data were used from the Dutch National Survey of General Practice ('87/'88),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
2
26
1
Order By: Relevance
“…Research showed that it depends upon the type of behaviour which health literacy skills are required. Different types of health literacy, be they functional, communicative or interactive, or critical, have a different impact upon different outcome measures [45,46]. Our results are in line with this.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Research showed that it depends upon the type of behaviour which health literacy skills are required. Different types of health literacy, be they functional, communicative or interactive, or critical, have a different impact upon different outcome measures [45,46]. Our results are in line with this.…”
Section: Discussionsupporting
confidence: 88%
“…One possible explanation for this might be that our respondents in general scored quite high on these lower order competences. It has also been suggested that the functional, communicative or interactive and critical components of health literacy can be seen as complementary [45]. Research showed that it depends upon the type of behaviour which health literacy skills are required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations